Compulsory Citizenship Behavior: Theorizing Some Dark Sides of the Good Soldier Syndrome in Organizations - VIGODA-GADOT, ERAN (Journal for the theory of social behaviour, 2006)
The most prominent characteristic of good citizenship behavior is the willingness of individuals to invest effort and energy in their social environment beyond any formal requirement and with no expectation of formal rewards. When studied in the workplace, this behavior has been called Organizational Citizenship Behavior (OCB) and has become the subject of many works that have focused on the positive connotations of the 'good soldier syndrome.' A majority of the 270 studies published in recent decades about OCB have pointed to the benefits and advantages of voluntary helping behaviors, pro-social behavior, altruism and extra-role behavior. In contrast with this view, the present paper suggests that OCB also has darker aspects, one of which is the exploitative and abusive tendency of supervisors and managements to impose so-called 'voluntary' or `extra-role' activities via compulsory or coercive mechanisms in the workplace. The paper focuses on such exploitation and abusiveness and their potential impact on employees' performance. It is argued that frequently individuals engage in so-called OCBs not as a matter of free choice or good will, but as a result of considerable social pressure by powerful others, be they managers or other co-workers. It is suggested that such behaviors can be placed on a continuum of extra-role behaviors, but that they should also be recognized as a substantial deviation from the original meaning of OCB and thus should be examined and analyzed separately. Reprinted by permission of Blackwell Publishers